Bisphenol A degradation using waste antivirus copper film with enhanced sono-Fenton-like catalytic oxidation - Chu, Jae Hun; Kang, Jin Kyu; Park, Seong Jik; Lee, Chang Gu (Chemosphere, 2021)
This study investigated the applicability of waste antivirus copper film (CF) as a Fenton-like catalyst. The reaction activity of H2O2 and CF in combination was significantly enhanced by ultrasound (US) irradiation, and the synergy factor calculated from bisphenol A (BPA) degradation using CF-H2O2-US was 9.64 compare to that of dual factors. Photoluminescence analyses were conducted to compare the generation of hydroxyl radicals during both processes. In this sono-Fenton-like process, BPA degradation was affected by solution pH, temperature, ultrasound power, CF size, H2O2 dose, and initial BPA concentration. The BPA degradation curves showed an induction period (first stage) and a rapid degradation period (second stage). Process efficiency was totally and partially enhanced in the presence of chloride and carbonate ions, respectively. Chemical scavenger tests showed that both free and surface-bound hydroxyl radicals participate in BPA degradation under the sono-Fenton-like process using CF. The functional groups and copper crystals on the CF surface remained unchanged after five consecutive reuses, and the BPA degradation efficiency of CF was maintained over 80% during the reuse processes as a sono-Fenton-like catalyst.
Keywords: Anti virus; Antivirus copper film; Bisphenol A; Bisphenols-A; Copper films; Fenton likes; Fenton-like oxidation; H$-2$/O$-2$; Hydroxyl radicals; Sono-fenton; Benzhydryl Compounds; Copper; Hydrogen Peroxide; Oxidation-Reduction; Phenols; Antivirus copper film; Bisphenol A; Fenton-like oxidation; Hydroxyl radicals; Ultrasound